Angelologia e burocrazia: tecnologie del potere amministrativo - Catanzariti, Benedetta (Filosofia, 2017)
The present paper considers the angel from the Christian tradition as a political figure; the theological development of its image, its configurations, and its lexicon, all pave the way to the realms of bureaucracy and administration, i.e., to the subjection of life to power. As the theologico-political perspective emerging with Carl Schmit has shown, this is not a unidirectional process – i.e., the relation- ship between theological and political concepts is not simply one of historical con- tinuity but, rather, a bidirectional one of structural analogy. In this regard, angelol- ogy represents the theorization of those beings appointed to rule administratively on human matters. In this case, life management would consist in an asymmetric relationship of visibility between the surveillant – the guardian angel – and the individual under surveillance.